Clinical Spectrum- Cognition, Stages, Functionality among Elderly with Dementia: A Cross-Sectional Study - Niroula, Niju (Journal of Nepalgunj Medical College, 2020)
Introduction: Although cognitive and functional impairment are the hallmark features of Dementia but it is often undetected and neglected as a normal part of aging. So we conducted this study on clinical profile of dementia patients. Aims: The aim of this study is to evaluate the Patient’s cognitive impairment, functional capacities, and stages of severity of dementia. Methods: A descriptive cross sectional study was conducted among 50 patients aged 60 years and above, of both sexes with the diagnosis of Dementia, admitted in Medicine ward of Nepalgunj Medical College, Nepalgunj, Nepal. The screening of dementia was done using Mini-Mental State Examination tool and the diagnosis of Dementia was confirmed using the International Classification of Disease-10 Diagnostic Criteria for Research. Cognition, functionality and stages of severity of dementia were assessed using Hierarchic Dementia Scale, Functional Autonomy Measurement System, Functional Assessment Staging Test tools respectively. Results: Among a total of 50 dementia patients, the mean and standard deviation of age was 82.4±6.1 years, majority of cases 60 % were in the age group ≥85 years and most patients were female 56%. The mean Mini-Mental State Examination score was 9.6±3.0, and 50 % had severe impairment of cognition on Hierarchic Dementia Scale. Stage 7 dementia 32 % was most prevalent stage on Functional Assessment Staging and severe deterioration in the functional autonomy was seen in 54% dementia patients (score ≥41 on Functional Autonomy Measurement System). Conclusion: This study concludes that significant number of elderly patients attending tertiary care hospital suffers from dementia with severe impairment in cognition and functionality in various stages of dementia in the elderly patients.